e-Portfolio system development for integrating students’ capability: a conceptual framework / Prasanna Ramakrisnan, Siti Sapura Jailani and Mohd Yuzi Zali - Ramakrisnan, Prasanna; Jailani, Siti Sapura; Zali, Mohd Yuzi (UiTM Press, 2018)
An electronic portfolio which is known as e-portfolio or digital portfolio is a collection of electronic document describing knowledge, skills, experience, abilities, progress or achievement of a person. The purpose of this paper is to propose a conceptual framework to develop e-portfolio to showcase the students’ capability to the industries. This framework will be used at one Higher Education (HE) institution in Malaysia as a guideline for e-portfolio system development. Recently, the initiative of HE Ministry in Malaysia to make students’ e-portfolio available at all the public universities have received numerous enquiries for establishing the e-portfolio system in their institutions. A wide literature search was conducted to review on the existing framework for e-portfolio system development. The finding showed that there was a lack of guidance for development of student e-portfolio framework. Therefore, this research discussed a conceptual framework involved in the student e-portfolio system development. The conceptual framework was based on literature review and previously developed frameworks. It is hoped that this framework will be used by other institutions for developing e-portfolio system in the future.